(untitled) (Third Sector Social Economic Review, 2021)
Foreign Direct Investment (FDI) is a key source of foreign exchange, new jobs and bleeding-edge technology transfers for the developing countries. However, terrorist attacks in a country are an important factor determining the preferences of companies in investing abroad. Turkey has been facing both internal and external terrorist groups’ attacks since the late 1980s. In this context, this study discussed the impact of terrorism on FDI inflows in Turkey for the period 1990-2019. Autoregressive Distributed Lag (ARDL) bounds testing approach to co-integration was used in the study. The study revealed that terrorism affects FDI in Turkish economy positively and not significantly in the short-run, while negatively and significantly in the long-run. Furthermore, the impact of some supportive variables- inflation, trade openness, military expenditure and remittances on FDI and terrorism in the model was also examined in the paper. The results concluded that trade openness shows the negative and significant impact on FDI both in the short run and long run. Remittances shows negative and significant result. This indicate that there is a short run negative relationship between remittances and FDI. Inflation shows positive but not a significant impact on FDI, and military expenditure also shows negative and non-significant impact in the short run, which normally has to be positive.